THE CHANGE OF PROPERTIES OF BLACKCURRANT BERRIES EXTRACTS DURING THE EVAPORATION PROCESS - Igor Alekseevich Bakin; Anna Sabirdsynovna Mustafina; Leonid Alekseevich Aleksenko (Современная наука и инновации)
The article discusses the results of a study of the physical properties of aqueous and hydroalcoholic extracts of black currant during the process of concentration in the evaporator, the rotary type. Regression equations of the influence of regime parameters of evaporator for concentration changes of soluble solids in the extracts, it was revealed that with increasing concentration of soluble solids in the extracts of their density and viscosity increase. The viscosity of the extracts is in direct proportion to the alcohol concentration in the extractant and feedback from the process temperature, which is related to the content in the extracts polyphenolic substances containing ionized groups causes the molecular interaction force is repulsive. It is revealed that due to careful processing mode extracts the concentrate is characterized by a high content of biologically active substances. Recommendations on the rational values of technological parameters and operating conditions of the evaporation process in a thin film under vacuum, derived empirical relationships recommended to use when calculating the evaporators rotary.